Analysis and Experimental Study of a Seven level Inverter - Putra Wijaya, Voni; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The demand for electrical energy continues to increase and has become an essential part of daily human activities. To support the use of environmentally friendly energy, the utilization of renewable energy sources such as solar panels is increasingly prioritized. However, since solar panels generate only direct current (DC), a device is needed to convert it into alternating current (AC) to ensure compatibility with most household appliances. Inverters serve as the primary solution for this conversion process. Although full-bridge inverters are commonly used, they still produce a relatively high level of harmonic distortion. Therefore, the multilevel inverter approach is considered more effective in improving the quality of the output voltage. This study proposes the design and implementation of a single-phase 7-level inverter using a cascaded H-bridge topology. This topology was chosen due to its modular structure, which allows for the generation of output waveforms that closely resemble a sinusoidal shape. The system is controlled by an Arduino Mega 2560 microcontroller using a PWM switching technique. Testing was conducted after completing simulation stages using MATLAB/Simulink and building the hardware prototype. Based on the experimental results, the inverter successfully produced stepped waveforms with relatively low harmonic distortion levels, with a current THD of 8.33% and a voltage THD of 23.95%. The system's stable performance indicates that this design has potential for application in small scale renewable energy systems, such as residential solar power generation